Report of a Rare Case of Epitheliod Hemangioendothelioma in Tongue - Manas Bajpai; Nilesh Pardhe (Shiraz University of Medical Sciences, 2019)
Epitheloid hemangioendothelioma (EHE) is a rare vascular neoplasm of intermediate malignant potential. EHE commonly involves lungs, liver soft tissue, and bone. EHE is extremely rare in tongue and up to our best knowledge only nine cases of EHE of tongue reported in the literature. Clinicallyو EHE usually presents as an asymptomatic mass. Microscopically, EHE exhibits proliferation of epitheloid cells and spindle shaped endothelial cells. Epitheloid cells show cytoplasmic vacuoles with few cells containing RBCs. A 34-year-old male presented to our institution with the chief complain of swelling on the base of the tongue from eight months. Surgical excision was done. An extensive work up of immunohistochemistry was done using different markers including CD 31, CD 34, Ki 67, Factor VIII, and BCL2. Correlation of histopathology and immunohistochemistry confirmed the diagnosis of EHE. The follow up period of 2 years was uneventful.